Asia-Pacific population journal 1986-2009 complete collection. - United Nations. Economic and Social Commission for Asia and the Pacific. Population Division; United Nations Fund for Population Activities (Population Programme of the United Nations Economic and Social Commission for Asia and the Pacific.)
Abstracts and full-text articles covering all aspects of population issues including birth control, women and population, population planning, poverty and development issues, and migration. Print equivalent ISSN: 0259-238X. Selected issues of electronic version available since 1990. Can search for articles by issue, broad subject or general search.
Title from disc label.
Keywords: Demography -- Asia -- Periodicals; Asia -- Population -- Periodicals; Pacific Area -- Population -- Periodicals